Optimasi Fuzzy Time Series Untuk Peramalan Kebutuhan Hidup Layak Kota Kediri Dengan Menggunakan Algoritme Genetika - Tahajuda Mandariansah; Budi Darma Setiawan; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Proper living needs (KHL) is a standard requirement for a worker or single person physically can live well for the needs of one month, the value of KHL is one of the five minimum wage determinataion factors. The value of KHL is determined based on survey value from january to september, while in determining regional minimum wage (UMR) shall be done no later than 60 days or two months before january 1st of the following year. Therefore it's necessary to forecast the value of KHL. This forecasting is helpful for the goverment in the process of determining UMR. In forecasting using fuzzy time series method optimized with genetic algorithm. The optimization is done on the interval value in the fuzzy time series method to get good accuracy in forecasting. Based on the results of tests on value of KHL Kediri from 2009 to 2015, using the parameter of the interval number 7, using the combination of Cr 0.9 and Mr 0.5, the population number 1050, and the number of generations 100 using the average forecasting error rate (AFER) has obtained an error value of 4.7211%